AI, IoMT and Blockchain in Healthcare - Sarker, Bipasha; Sharif, Numair Bin; Rahman, Mohammad Atikur; Parvez, A.H.M. Shahariar (Journal of Trends in Computer Science and Smart Technology, 2023)
The healthcare industry is adopting new technologies such as AI, IoMT, and blockchain to enhance patient outcomes, reduce costs, and improve operational efficiencies. These technologies can revolutionize healthcare by facilitating personalized patient-focused care, improving clinical outcomes, and reducing expenses. However, the implementation of these technologies requires collaboration between healthcare providers, technology companies, and regulatory bodies to ensure patient privacy and data security. This study explores the role of AI, IoMT, and blockchain in public healthcare and their current applications, obstacles, and future research areas. It emphasizes the advantages that these technologies bring to the IoT and the difficulties involved in their implementation.
Keywords: Internet of Medical Things (IoMT); Internet of Things (IoT); Machine Learning (ML); Deep Learning (DL); Artificial Intelligence (AI); Blockchain